Mesenchymal Stem Cells for Enhancing Biologic Healing after Anterior Cruciate Ligament Injuries - Jang, Ki-Mo; Lim, Hong C.; Hoon Bae, Ji (Current Stem Cell Research & Therapy, 2015)
Arthroscopic anterior cruciate ligament (ACL) reconstruction using tendon grafts is the current gold standard for the treatment of ACL tears in active patients. However, many patients still experience residual knee instability, knee pain and progressive cartilage degeneration following ACL reconstruction. Recent developments in mesenchymal stem cell (MSC)-based approaches for treating musculoskeletal injuries have led to the application of MSCs for enhancing healing after ACL injuries. The purpose of this article is to review recent pre-clinical and clinical studies using MSCs for the enhancement of biologic healing of ACL injuries. Because of the success of pre-clinical studies, MSC-based approaches are now thought to be promising treatment options for enhancing biologic healing of ACL grafts and restoring the functional properties to the levels of the native ACL, and ultimately improving clinical outcomes.
Keywords: anterior cruciate ligament reconstruction